Enantioselective approach to indolizidine and quinolizidine scaffolds. Application to the synthesis of peptide mimics. Issue 1 (4th January 2018) - Lu, Yuanyuan; Alujas-Burgos, Sílvia; Oliveras-González, Cristina; Vázquez-Jiménez, Laura; Rojo, Pep; Álvarez-Larena, Ángel; Bayón, Pau; Figueredo, Marta
Abstract: An enantioselective approach to substituted indolizidine and quinolizidine frameworks has been developed. Key steps of the synthesis are the enantioselective, palladium-catalyzed N -allylation of an imide, the nucleophilic allylation of an acyliminium ion and a ring closing metathesis. This general strategy has been applied to the synthesis of indolizidine peptide mimics, starting from a chiral imide derived froml -aspartic acid. It was observed that the preexisting stereogenic center of this substrate has a moderate influence on the stereoselectivity of the electrophilic allylation, which is mainly determined by the sense of chirality of the catalyst. Graphical abstract: